A Preliminary Study on Control Indices and Emission Limits of Substation Noise - Zhang Xiang; Chen Xingwang; Fang Xiaojian; Shi Yuzhu; Lu Lingyun; Chen Yuhua; Di Guoqing (E3S Web of Conferences)
A-weighted networks underestimate the impact of low-frequency noise to some extent. Substation noise is a typical low-frequency noise with several tonalities, so it is necessary to further optimize the control indices and emission limits of substation noise. 280 subjects were randomly recruited, and 111 noise samples from 110-1000 kV substations were used to carry out listening tests of noise annoyance. The mean noise annoyance (Ā) of each sound sample was obtained, and the models between any two of Ā, NR, and LAeq were established respectively. The limits of LAeq of Classes 1-4 functional areas of sound environment in GB 12348-2008 were substituted into the afore-mentioned models to determine the NR number. Based on the NR curve, the control limits of sound pressure level of substation noise were determined at each 1/1 octave band from 31.5 Hz to 500 Hz. Results showed that Ā increased by about 1 for every 5 dBA increase in LAeq when LAeq was 45-70 dBA. At the same LAeq, Ā of 750-1000 kV substation noise was 0.24-1.59 higher than that of 110-500 kV substation noise. It was recommended to divide substations into two groups according to their voltage levels. Meanwhile, the day-time and night-time control values of Ā were clarified if the limits of LAeq in Classes 1-4 were implemented. The results can provide a basis for controlling low-frequency noise in substations.